2004
DOI: 10.1590/s0004-282x2004000500012
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic cerebrovascular disease in childhood: cognitive assessment of 15 patients

Abstract: The aim of this study was to evaluate and to compare the cognitive function of children with ischemic cerebrovascular disease (ICVD). Fifteen children, 7 girls and 8 boys, aged 7.9 to 16.1 years, were evaluated by Piaget's clinical method. The control group was composed by fifteen children whose ages, sex and socioeconomic conditions were similar to those of the ICVD group. The cognitive function evaluation of the ICVD group showed that most of the children (10/15) were under their age group. The SPECT was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
10

Year Published

2005
2005
2009
2009

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 10 publications
0
2
0
10
Order By: Relevance
“…90,91 Recurrence rates are high, justifying early diagnosis and primary or secondary preventative measures to reduce these complications. No standard treatment schemes have yet been proposed for managing stroke in children, with the majority of data having been drawn from consensus by specialists or extrapolated from reports in the literature on adult patients.…”
Section: Discussionmentioning
confidence: 99%
“…90,91 Recurrence rates are high, justifying early diagnosis and primary or secondary preventative measures to reduce these complications. No standard treatment schemes have yet been proposed for managing stroke in children, with the majority of data having been drawn from consensus by specialists or extrapolated from reports in the literature on adult patients.…”
Section: Discussionmentioning
confidence: 99%
“…O diagnóstico do AVE é desafiador, particularmente em faixas etárias pediátricas mais jovens porque os sintomas frequentemente são pouco específicos. Sequelas neurológicas e comprometimentos neuropsicomotores de longo prazo são comuns, estando intimamente ligados à doença de base e à extensão das lesões cerebrais 90,91 .…”
Section: Conclusõesunclassified
“…De Schryver et al 5 found impaired capacity for solving problems in post CVA children, when compared to the general population. Rodrigues et al 8 described children with CVA assed evolutionally by Piaget´s clinical method had present a performance significantly inferior when compared to the control group. The sequelae of a CVA during childhood are not yet as widely known as of one during adulthood; however, the more studies there are in the area, the more details shall be discovered, favoring professionals involved in the rehabilitation of such children 9 .…”
mentioning
confidence: 99%